2008
DOI: 10.1007/s00540-007-0581-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary capillary leak syndrome during elective surgery under general anesthesia

Abstract: A 75-year-old previously healthy man presented for elective resection of rectal cancer under general anesthesia. Six days before the operation, he had a high-grade fever, and elevated leukocyte count and C-reactive protein concentration, but this was resolved by an intravenous antibiotic. His condition was well controlled before the operation. Soon after the operation started, severe hypoxemia emerged, with low arterial pressure. Fiberoptic bronchoscopy demonstrated a massive amount of plasma-like edema fluid;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…9,24,25 Surgery-related injury induces the release of proinflam- matory cytokines, such as tumor necrosis factor α (TNFα), vascular endothelial growth factor (VEGF), many interleukins, histamine, and E-selectine, which may disturb vascular permeability, and increase fluid shift into the extravascular space. 26,27 Moreover, surgery-related perioperative stress induces the release of antidiuretic hormone, cortisol and corticotrophins, and stimulates the renin-angiotensin-aldosterone system to increase salt and fluid retention. 28,29 Therefore, a surgery-induced increase in vascular permeability and hormone-dependent fluid retention provoke perioperative tissue edema independently of fluid infusion.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,25 Surgery-related injury induces the release of proinflam- matory cytokines, such as tumor necrosis factor α (TNFα), vascular endothelial growth factor (VEGF), many interleukins, histamine, and E-selectine, which may disturb vascular permeability, and increase fluid shift into the extravascular space. 26,27 Moreover, surgery-related perioperative stress induces the release of antidiuretic hormone, cortisol and corticotrophins, and stimulates the renin-angiotensin-aldosterone system to increase salt and fluid retention. 28,29 Therefore, a surgery-induced increase in vascular permeability and hormone-dependent fluid retention provoke perioperative tissue edema independently of fluid infusion.…”
Section: Discussionmentioning
confidence: 99%
“…SCLS is diagnosed clinically after exclusion of wide variety of diseases that cause systemic capillary leak such as infections, hereditary angioedema, chemotherapy, malignancy, drugs, anesthesia, and surgery with laboratory evidence of the plasma leak. 4 , 6 , 7 , 8 Hemoconcentration and hypoalbuminemia are the cornerstones of the diagnosis. Dhir et al has reported laboratory features of SCLS, that hematocrit was recorded to be high, 63.5±8.65%; serum albumin was mentioned to be low to 1.67±0.66 g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…According to the “two hit hypotheses”, the bacterial infection preceding the operation may prime the immune cells and the following surgical stress may then trigger sudden massive pulmonary capillary leak leading to ARDS during elective surgery even though the patient’s condition is well controlled. [7]…”
Section: Discussionmentioning
confidence: 99%
“…[2] Less appreciated is the fact that various drugs, either taken as standard therapy or as an overdose, may precipitate NCPE. [7] Little is known about the mechanisms involved in drug related NCPE.…”
Section: Introductionmentioning
confidence: 99%